Biomechanical effects of Skeletally anchored Class III elastics on the maxillofacial complex: a 3D finite element analysis - Priyank Rai; Dhiraj Garg; Tulika Tripathi; Anup Kanase; Gayatri Ganesh (SpringerOpen, 2021)
Abstract Background Although, the outcomes and changes in the maxillofacial complex after the application of intraoral bone anchored Class III elastics, have been reported by multiple clinical studies, there was no finite element study to assess and evaluate the stress pattern and displacement on maxillomandibular complex with bimaxillary anchorage. The present study aims to evaluate the biomechanical effects on maxillomandibular complex of Skeletally anchored Class III elastics with varying angulations using the 3D finite element analysis. Methodology Two 3-dimensional analytical models were developed using the Mimics 8.11 (Materialise: Leuven, Belgium) and ANSYS software Version 12.1 (ANSYS Inc, Canonsburg, PA, USA) from sequential computed tomography images taken from a Skeletal Class III subject. The models were meshed into 465,091 tetrahedral elements and 101,247 nodes. Intraoral mechanics for skeletally anchored maxillary protraction (I-SAMP) were applied on two models i.e. A and B (without and with maxillary expansion respectively) between miniplates on maxilla and mandible on both right and left sides with three different angulations of forces-10°, 20° and 30°). Results Although the craniomaxillary complex in both the models (A and B) displaced forward while demonstrating rotations in opposite directions, the displacements and rotations decreased gradually with the increase of the angle of load application from 10° to 30°. The mandible rotated clockwise in both the simulations, but the displacement of mandibular surface landmarks was higher in Simulation A. However, the antero-inferior displacement of the glenoid fossa was higher in Simulation B than in A. Conclusion Significant displacement of maxillofacial sutures and structures was witnessed with I-SAMP with maxillary expansion and Class III elastics for correction of Skeletal Class III with maxillary retrognathism. Thus, I-SAMP with maxillary expansion is a desired protocol for treatment of maxillary retrognathism. However, the prescribed angulation of the Class III elastics should be as low as possible to maximise the desired effects.